2022
DOI: 10.1007/s00402-022-04422-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 disruptions to elective postoperative care did not adversely affect early complications or patient reported outcomes of primary TKA

Abstract: Introduction Elective orthopedic care, including in-person office visits and physical therapy (PT), was halted on March 16, 2020, at a large, urban hospital at the onset of the local COVID-19 surge. Post-discharge care was provided predominantly through a virtual format. The purpose of this study was to assess the impact of postoperative care disruptions on early total knee arthroplasty (TKA) outcomes, specifically 90-day complications, 120-day rate of manipulation under anesthesia (MUA) and 1-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Moreover, no study has demonstrated the effect of COVID-19 infection within 1 week after TKA on early clinical outcomes and complications. Recent studies have reported that previous COVID-19 infections do not adversely PROMs or complications of primary TKA [ 10 , 11 ].The findings of the current study are consistent with those of previous studies and indicate no significant difference in PROMs between the two groups, even if infection occurred within 1 week after TKA. Furthermore, although previous studies have shown a higher incidence of postoperative complications after TKA for previous COVID-19 infection [ 29 , 30 ], in our study, no difference was found between the groups in terms of pneumonia and other significant complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, no study has demonstrated the effect of COVID-19 infection within 1 week after TKA on early clinical outcomes and complications. Recent studies have reported that previous COVID-19 infections do not adversely PROMs or complications of primary TKA [ 10 , 11 ].The findings of the current study are consistent with those of previous studies and indicate no significant difference in PROMs between the two groups, even if infection occurred within 1 week after TKA. Furthermore, although previous studies have shown a higher incidence of postoperative complications after TKA for previous COVID-19 infection [ 29 , 30 ], in our study, no difference was found between the groups in terms of pneumonia and other significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that a history of COVID-19 infection does not appear to increase the risk of VTE following primary TKA [ 10 ]. Furthermore, a recent study reported that COVID-19 did not adversely affect early complications or patient-reported outcomes measures (PROMs) after TKA [ 11 ]. However, all these studies were conducted on patients who had COVID-19 infection before TKA; further, the timing of infection before the surgery was not constant [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the current evolution of the COVID-19 pandemic, the primary need is to properly allocate resources (staff, beds, ICU beds, economic resources, post-discharge care, etc.) [ 45 ] and contain the pandemic spread. However, given the continuing and recurring constraints, secondarily in the long term, it is also necessary to find strategies and ways to allow elective surgery to avoid the far-reaching consequences that arise from surgical delays.…”
Section: Discussionmentioning
confidence: 99%
“…One study saw a significant correlation between inferior clinical outcomes at 6 months and missed physiotherapy 31 . Another study saw that despite decreased care access and post-surgical PT compared with pre-pandemic patients, 1-year clinical outcomes were equivalent 32 . This highlights that there may be an over-emphasis on in-person follow-up and PT for post-arthroplasty patients and requires future exploration in the future.…”
Section: Arthroplasty During Covid-19mentioning
confidence: 99%